Clinical characteristics and disease burden in prurigo nodularis. (1st October 2021) - Aggarwal, P.; Choi, J.; Sutaria, N.; Roh, Y. S.; Wongvibulsin, S.; Williams, K. A.; Huang, A. H.; Boozalis, E.; Le, T.; Chavda, R.; Gabriel, S.; Kwatra, S. G.
Summary: Background: Prurigo nodularis (PN) is a chronic inflammatory skin disease characterized by intense pruritus, but information on patient experience and impact on quality of life (QoL) remains understudied. Aim: To characterize disease characteristics and QoL in a global sample of patients with PN. Methods: An anonymous survey was distributed via patient support groups for PN. Results: In total, 231 members responded to the survey. The majority of respondents reported itch localized both to nodules and to intervening skin (67.0%). Associated symptoms included prickling, pain, stinging and burning. The extensor lower legs (69% right, 67.3% left) and flexor forearms (66.1% right, 62% left) were the most common sites of itch. Participants reported frequent healthcare utilization, with 36.3% visiting a doctor ≥ 10 times in the past year. Physician‐diagnosed anxiety (45.4%), depression (16.4%) and the atopic triad (18.7%) were commonly reported. Patients with PN had mean scores of 16.4, 11.6 and 16.8 on the Dermatology Life Quality Index, Pittsburgh Sleep Quality Index and 5‐Dimensions Itch, respectively. Conclusions: Severe pruritus with accompanying pain, stinging and burning is characteristic of PN, with the majority of patients experiencing itch in both nodular and interlesional skin. Patients further report decreased QoL scores and impaired sleep. Patient experiences should guide future management of PN.